2011
DOI: 10.3393/jksc.2011.27.3.107
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Prolapse: Review According to the Personal Experience

Abstract: The aim of treatment of rectal prolapse is to control the prolapse, restore continence, and prevent constipation or impaired evacuation. Faced with a multitude of options, the choice of an optimal treatment is difficult. It is best tailored to patient and surgeon. Numerous procedures have been described and are generally categorized into perineal or abdominal approaches. In general, an abdominal procedure has associated with lower recurrence and better functional outcome than perineal procedures. The widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…Yoon proposed a combined Delorme-Thiersch procedure for rectal prolapse; this combined procedure had comparatively improved outcomes for high-risk patients in his series, and no recurrence was reported during a mean follow-up period of 22 months. 15 Gupta proposed another combined method: Thiersch's procedure and subanodermal coagulation. The recurrence rate is 7.9% (3/38) after 2 years follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon proposed a combined Delorme-Thiersch procedure for rectal prolapse; this combined procedure had comparatively improved outcomes for high-risk patients in his series, and no recurrence was reported during a mean follow-up period of 22 months. 15 Gupta proposed another combined method: Thiersch's procedure and subanodermal coagulation. The recurrence rate is 7.9% (3/38) after 2 years follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic leakage has been found to be very rare. [7]. Agachan et al reported that addition of levatorplasty during Altemeier's procedure leads to less chances of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why patients with rectal prolapse suffer from not only a prolapsed rectum but also associated dysfunction. A large percentage of patients suffering from rectal prolapse also complain from faecal incontinence (FI), obstructed defecation and chronic constipation; in this patients the frequent straining during defecation induces an injury of the rectal mucosa, often leading to rectal ulcer development [3]. FI in external rectal prolapse has two different components: the prolapsed mucosa generates a continuous secretion that causes a soiling that can be serous-mucous as well as seroushaematic in case of mucosal ulcers and erosions; the stretching of the muscles induces a progressive weakness of the sphincters affecting their resting tone and reducing their contractile strength.…”
Section: Introductionmentioning
confidence: 99%